From macrophyte to algae: Differentiated dominant processes for internal phosphorus release induced by suspended particulate matter deposition. (1st October 2022) - Liu, Cheng; Du, Yiheng; Zhong, Jicheng; Zhang, Lei; Huang, Wei; Han, Chao; Chen, Kaining; Gu, Xiaozhi
Highlights: P release in the macrophyte- (MDA) and algae-dominated (ADA) areas were studied. Particulate matter led to discrepant sedimentation and dissolution processes of P. P release in the MDA was mainly controlled by Fe-P coupling with Fe, S, and P. In the ADA, it was controlled by both Org-P and Fe-P, with Org-P prevailing. Org-P control might be intensified with a shift from macrophyte to algae. Abstract: In shallow lakes, eutrophication leads to a shift of the macrophyte-dominated clear state towards an algae-dominated turbid state. Phosphorus (P) is a crucial element during this shift and is usually concentrated in the suspended particulate matter (SPM) in water. However, the dominant processes controlling internal P release in the algae- (ADA) and macrophyte-dominated (MDA) areas under the influence of P-concentrated SPM remains unclear. In this study, we conducted monthly field observations of P exchange across the sediment-water interface (SWI) with the deposition of SPM in the ADA and MDA of Lake Taihu. Results revealed that both algae- and macrophyte-originated SPM led to the depletion of oxygen across the SWI during summer and autumn. Redox-sensitive P (Fe-P) and organic P (Org-P) were the dominant mobile P fractions in both areas. High fluxes of P across the SWI were observed in both areas during the summer and autumn. However, the processes controlling P release were quite different. In MDA, P release was mostly controlled by a traditional Fe-P dissolution process influenced by the coupled cycling of iron, sulfur, and P. In the ADA, Org-P control was intensified with the deterioration of algal bloom status, accompanied with the dissolution of Fe-P. Evidence from the current study revealed that the dominant process controlling the internal P release might gradually shift from Fe-P to a coupled process of Fe-P and Org-P with the shift of the macrophyte- to an algae-dominated state in shallow eutrophic lakes. The differentiated processes in the MDA and ADA should be given more attention during future research and management of internal P loadings in eutrophic lakes. Graphical abstract: Image, graphical abstract